Performance of Village Officials in Government Administration in Huristak District, Padang Lawas Regency: Viewed from an Islamic Perspective - Harahap, Siti Mahrani; Nasution, Hasan Bakti; Harahap, Mardian Idris (Borong Newinera Publisher, 2024)
This study seeks to analyze the performance of village officials in governance from an Islamic perspective. This study aims to analyze the performance of village officials in governance in Huristak District, Padang Lawas Regency, focusing on Islamic perspectives. The research method used is a qualitative approach using in-depth interviews, observation, and documentation. The study respondents involved village officials, community leaders, traditional leaders and local religious leaders. The collected data is analyzed through a contextual approach and reviewed from an Islamic point of view. The results of this study show that the performance of village officials in the context of governance has achieved maximum results. This assessment is based on the understanding and implementation of Islamic principles in village governance. In various limitations, village officials have succeeded in establishing strong community participation mechanisms in decision making, creating fair public services, and ensuring accountability and transparency in every policy taken. The involvement of religious leaders in the decision-making process is also a determining factor in achieving maximum results. The initiative helps to effectively integrate Islamic values in all aspects of village governance. In addition, close collaboration between village officials, community leaders, and clerics has contributed positively to sustainable development and community welfare. The implications of the results of this study can be used as a reference for local governments, village officials, and other stakeholders to strengthen and maintain the success that has been achieved in presenting governance in accordance with Islamic values in Huristak District and its surroundings.